Mindful sharenting: how millennial parents balance between sharing and protecting - Walrave, Michel; Robbé, Sofie; Staes, Luna; Hallam, Lara (Frontiers in Psychology, 2023)
Background Sharenting, parents’ sharing of personal information about children on social media is becoming increasingly controversial. Its potential risks have drawn some parents to engage in mindful sharenting: parents’ application of strategies to reduce the potentially negative effects of sharenting, as they are aware of the impact sharenting can have on the child’s privacy. Objective This study aims to investigate parents’ motives for engaging in mindful sharenting, the strategies they implement and how relatives and acquaintances react. Methods In-depth interviews were conducted with eight mother–father dyads in Belgium. At least one of both respondents had to be born between 1980 and 2000 (i.e., millennial parents), having a child aged between 0 and 6 years. Conversations were transcribed ad verbatim, coded in Nvivo, and were analyzed thematically. Results The reasons leading parents to engage in mindful sharenting were previous negative experiences they encountered or heard of from acquaintances. In addition, parents aimed to safeguard their child’s privacy and prevent any misuse of their identity or any other forms of aggression. Furthermore, certain parents wish to grant their children the freedom to choose which media content about them is shared online at a later stage in life. As parents are aware of potential benefits of sharenting, they employ strategies to ensure their child’s privacy, while still enjoying the benefits sharenting offers them. These strategies include photographing the child from a distance, the child looking away from the camera, focusing only on a body part, covering the face with an emoticon, blurring the face, or cutting recognizable parts from the photo. However, parents engaging in mindful sharenting are also confronted with questions and negative comments from family members and acquaintances. This makes them feel like they must justify their decision. Moreover, they are sometimes confronted with family members posting identifiable pictures of their child, which leads to privacy turbulence, and parents having to clarify and renegotiate the privacy boundaries concerning image sharing. Conclusion Parents deciding to engage in mindful sharenting engage in several strategies to balance between the opportunities sharenting can offer them, the social pressure they experience to post child-related updates, and their objective to protect their child’s privacy. However, some parents face criticism, making them feel pressured to justify their decision and having to clearly explain to family members not to make identifiable pictures of their child available online.